PISCICULTURE PRODUCTION IN ORÓS CITY, STATE OF CEARÁ - Pinheiro, Emmanuel Teixeira; Moura Fé, Marcelo Martins de; Nadae, Jeniffer de (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1183, 2021)
Pisciculture appears in contemporary times as an alternative for sustainable development. This research aimed to characterize the production of fish farming and the subjects involved in this activity in the regional section of the Orós reservoir, a homonymous municipality, the Ceará central-south region. It is a basic case study, with exploratory and descriptive objectives and a mixed approach. The participating subjects responded to an interview and presented the structures of their farms and the production records. The study reveals fish farming as a potential economic activity to be developed in the region. However, challenges such as relations with suppliers and employees, together with the uncertainty of water availability and the conflicting management of water resources make the activity risky for producers.